Fluorescence light-up AIE probe for monitoring cellular alkaline phosphatase activity and detecting osteogenic differentiation. Issue 26 (15th June 2016) - Cao, Feng-Yi; Long, Yue; Wang, Shi-Bo; Li, Bin; Fan, Jin-Xuan; Zeng, Xuan; Zhang, Xian-Zheng
Abstract : Three phosphorylated tetraphenylethylene (TPE) probes were synthesized for monitoring ALP activity in living stem cells and detecting osteogenic differentiation. Abstract : Alkaline phosphatase (ALP) is an important monophosphate hydrolase during cell mineralization and osteogenic differentiation. Though traditional methods are provided for evaluating the ALP expression in the fixed and lysed cells, at present it is still challenging to monitor the ALP activity in living cells. In this work, three phosphorylated tetraphenylethylene (TPE) probes (TPE-PA, TPE-2PA and TPE-4PA) with different numbers of –PO3 H2 groups were synthesized for monitoring the ALP activity. It was found that in aqueous solution, both the TPE-PA and TPE-2PA probes were highly sensitive to ALP. In the presence of ALP, they could be quickly hydrolysed, resulting in an aggregation-induced emission (AIE) to light up ALP. While in living cells, only TPE-2PA showed good cell penetrability and high fluorescence signal-to-noise ratio during osteogenic differentiation. This probe provides us a new strategy to screen the ALP activity in living stem cells for detecting osteogenic differentiation.